The genus Pupa Röding, 1798 (Mollusca, Gastropoda, Acteonidae) in New Caledonia with notes on Recent species - Valdés, Ángel; Feliciano, Kendall; Malaquias, Manuel A.e. (Zootaxa, 2023)
The study of newly collected, live specimens of Pupa (Acteonidae) from New Caledonia and French Polynesia, revealed the presence of six distinct species in this region, including an undescribed species. All these species are re-described and/or named using molecular and morphological evidence as well as a review of the literature and examination of photographs of the type material of described species. Moreover, a review of the literature and type material suggests the existence of six additional species from other geographic regions across the Indo-Pacific. Illustrations of all these species are provided as well as remarks on possible synonymies. This study is the first species-level review of this group using modern taxonomic techniques.